2020
DOI: 10.1609/aaai.v34i02.5545
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Birds with One Stone: Beating 1/2 for EFX and GMMS via Envy Cycle Elimination

Abstract: Several relaxations of envy-freeness, tailored to fair division in settings with indivisible goods, have been introduced within the last decade. Due to the lack of general existence results for most of these concepts, great attention has been paid to establishing approximation guarantees. In this work, we propose a simple algorithm that is universally fair in the sense that it returns allocations that have good approximation guarantees with respect to four such fairness notions at once. In particular, this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…While this preserves exact envy-freeness in the cake-cutting setting of Arunachaleswaran et al [3], in our setting we argue that inclusion-wise minimality preserves the EF1 property of P. We also argue that this iterative process terminates at a partial allocation P that satisfies the desired social welfare guarantee. Finally, we use the algorithm of Lipton et al [20] (see also [2]) to extend this partial EF1 allocation into a complete EF1 allocation without losing social welfare. The detailed algorithm is presented as Algorithm 2.…”
Section: The Case Of High Optimal Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…While this preserves exact envy-freeness in the cake-cutting setting of Arunachaleswaran et al [3], in our setting we argue that inclusion-wise minimality preserves the EF1 property of P. We also argue that this iterative process terminates at a partial allocation P that satisfies the desired social welfare guarantee. Finally, we use the algorithm of Lipton et al [20] (see also [2]) to extend this partial EF1 allocation into a complete EF1 allocation without losing social welfare. The detailed algorithm is presented as Algorithm 2.…”
Section: The Case Of High Optimal Welfarementioning
confidence: 99%
“…This generalizes the classical cut-and-choose protocol for dividing a cake between two agents, where one agent cuts the cake into two pieces, the other agent chooses a piece, and the first agent then receives the remaining piece. Even for agents with additive valuations over the goods, 2 MMS allocations may not exist [18,23]. However, under additive valuations, an allocation where each agent receives at least 3 /4-th of her maximin share-i.e., a 3 /4-MMS allocation-always exists [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…4 Similar approximations have been studied in the context of envy-freeness up to any good (EFX) (Plaut and Roughgarden, 2020;Amanatidis et al, 2020).…”
Section: Algorithmic Results For Complete Eq1 Allocationsmentioning
confidence: 93%

Equitable Division of a Path

Misra,
Sonar,
Vaidyanathan
et al. 2021
Preprint
“…We also study the case with a small number of items. For additive valuations, Amanatidis et al [3] showed that when m ≤ n + 2, there exists an EFX allocation. For general valuations, to the best of our knowledge, non-trivial results are not known.…”
Section: Our Contributionsmentioning
confidence: 99%